MELD‐GRAIL‐Na: Glomerular Filtration Rate and Mortality on Liver‐Transplant Waiting List. Issue 5 (29th January 2020) - Asrani, Sumeet K.; Jennings, Linda W.; Kim, W.R.; Kamath, Patrick S.; Levitsky, Josh; Nadim, Mitra K.; Testa, Giuliano; Leise, Michael D.; Trotter, James F.; Klintmalm, Goran
Abstract : Background and Aims: Among patients with cirrhosis awaiting liver transplantation, prediction of wait‐list (WL) mortality is adjudicated by the Model for End Stage Liver Disease–Sodium (MELD‐Na) score. Replacing serum creatinine (SCr) with estimated glomerular filtration rate (eGFR) in the MELD‐Na score may improve prediction of WL mortality, especially for women and highest disease severity. Approach and Results: We developed (2014) and validated (2015) a model incorporating eGFR using national data (n = 17, 095) to predict WL mortality. Glomerular filtration rate (GFR) was estimated using the GFR assessment in liver disease (GRAIL) developed among patients with cirrhosis. Multivariate Cox proportional hazard analysis models were used to compare the predicted 90‐day WL mortality between MELD‐GRAIL‐Na (re‐estimated bilirubin, international normalized ratio [INR], sodium, and GRAIL) versus MELD‐Na. Within 3 months, 27.8% were transplanted, 4.3% died on the WL, and 4.7% were delisted for other reasons. GFR as estimated by GRAIL (hazard ratio [HR] 0.382, 95% confidence interval [CI] 0.344‐0.424) and the re‐estimated model MELD‐GRAIL‐Na (HR 1.212, 95% CI 1.199‐1.224) were significant predictors of mortality or being delisted on the WL within 3 months. MELD‐GRAIL‐Na was a better predictor of observed mortality at highest deciles of disease severity (≥ 27‐40). For a score of 32 or higher (observed mortality 0.68), predicted mortality was 0.67 (MELD‐GRAIL‐Na) and 0.51 (MELD‐Na). For women, a score of 32 or higher (observed mortality 0.67), the predicted mortality was 0.69 (MELD‐GRAIL‐Na) and 0.55 (MELD‐Na). In 2015, use of MELD‐GRAIL‐Na as compared with MELD‐Na resulted in reclassification of 16.7% (n = 672) of patients on the WL. Conclusion: Incorporation of eGFR likely captures true GFR better than SCr, especially among women. Incorporation of MELD‐GRAIL‐Na instead of MELD‐Na may affect outcomes for 12%‐17% awaiting transplant and affect organ allocation.